2021
DOI: 10.3390/agronomy11061070
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Term Effects of Conservative Soil Management and Fruit-Zone Early Leaf Removal Treatments on the Performance of Nerello Mascalese (Vitis vinifera L.) Grapes on Mount Etna (Southern Italy)

Abstract: The aim of this study was to analyze the mid-term influence of minimum tillage (MT) combined with early leaf removal (ELR) on the performance of the black grapevine variety Nerello Mascalese (Vitis vinifera L.). The research was carried out from 2015 to 2018 in a vineyard located in the Mount Etna area, East Sicily, Southern Italy. An average of about 8000 cm2 of leaves were removed from the ELR vines, corresponding to a canopy defoliation of 44% in 2017 and 30% in 2018. As for the stem water potential of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Photosynthetically active radiation (PAR) incident on the leaf surface (Q leaf , µmol m −2 s −1 of photons) was determined simultaneously with the measurements of the eco-physiological variables, using the sensor coupled to the porometer chamber, always exposed perpendicularly to incident sunlight on the leaf surface throughout each reading. Moreover, leaf temperature (T l , • C) and CO 2 internal concentration (Ci, µmol mol −1 ) were also measured [46,47]. Following [48], the photosynthesis/transpiration ratio was taken as an estimation of instantaneous water use efficiency (WUE), and the ratio between photosynthesis/stomatal conductance, which is known as intrinsic water use efficiency, was calculated.…”
Section: Physiological Behavior and Vine Water Status Measurementsmentioning
confidence: 99%
“…Photosynthetically active radiation (PAR) incident on the leaf surface (Q leaf , µmol m −2 s −1 of photons) was determined simultaneously with the measurements of the eco-physiological variables, using the sensor coupled to the porometer chamber, always exposed perpendicularly to incident sunlight on the leaf surface throughout each reading. Moreover, leaf temperature (T l , • C) and CO 2 internal concentration (Ci, µmol mol −1 ) were also measured [46,47]. Following [48], the photosynthesis/transpiration ratio was taken as an estimation of instantaneous water use efficiency (WUE), and the ratio between photosynthesis/stomatal conductance, which is known as intrinsic water use efficiency, was calculated.…”
Section: Physiological Behavior and Vine Water Status Measurementsmentioning
confidence: 99%
“…The literature highlights the need for particular attention to vineyard management and therefore to the analysis of the life cycle delimited to the agricultural phase for grape production [15][16][17][18][19][20]. The research on the adoption of LCA in the wine sector has shown an unequivocal environmental hotspot in the agricultural phase [2] due to the wide use of different agronomic techniques [15][16][17][18][19][20], which require an extensive use of inputs [21].…”
Section: Environmental Impacts In the Agricultural Phasementioning
confidence: 99%
“…The scientific literature on the adoption of LCA in the agri-food sector has shown an unequivocal environmental hotspot in the agricultural phase [2]. The agricultural phase involves the adoption of different agronomic techniques, such as soil management, fertilization, weeding, irrigation, pruning and harvesting [15][16][17][18][19][20], which require a wide use of inputs such as fuel, fertilization, pesticides and water irrigation [21]. However, the transformation phase of wine production also generates environmental impact due to the packaging materials used [22].…”
Section: Introductionmentioning
confidence: 99%
“…These were due to the extensive olive orchards, as well as the consociations with livestock where possible [31]. For other species such as grapevines, minimum or zero tillage is commonly applied in order to regulate the vegetative and reproductive balance of vines and, in some cases, in order to reduce erosion and land degradation [32][33][34].…”
Section: Introductionmentioning
confidence: 99%